Application of a Geriatric Injury Protocol Demonstrates High Survival Rates for Geriatric Trauma Patients with High Injury Acuity. Issue 10 (October 2017) - Karamanukyan, Tigran; Pakula, Andrea; Martin, Maureen; Francis, Ashwitha; Skinner, Ruby
Geriatric trauma has historically been associated with poor outcomes, particularly in the setting of severe polytrauma. Although geriatric trauma protocols are common, there are limited data on their impact in patients with high injury severity. In this study, we sought to investigate the impact of a geriatric injury protocol on outcomes in patients with severe trauma acuity. Ninety-eight geriatric patients (age ≥65) admitted to our trauma center with injury severity scores (ISS) ≥15 comprised the study cohort. The mean age was 75 ± 7.7 yrs. The mean ISS was 25 ± 9.2, and the mean geriatric trauma outcome score was 150 ± 3. Mortality was 17 per cent and 70 per cent were due to central nervous system injury. When patients with nonsurvivable injuries or advanced directives resulting in early care withdrawal were excluded, the mortality was 6 per cent. Extremes of age did not impact mortality [(>80 years, 21%) vs (65–79, 16%, P = 0.5)]. Most patients (53%) were discharged home. The application of our geriatric trauma protocol led to favorable results despite high injury acuity. These data suggest that even at the extremes of age, a large percentage of patients can be expected to survive. A prospective validation of these findings is warranted.